(untitled) (Selecciones Matemáticas, 2024)
This paper describes certain types of prime submodules and maximal submodules that are found within the idealization of a module. As a consequence of this, it is concluded that every module over a commutative ring with identity element has an extension whose prime spectrum is nonempty.